POTRET SEJARAH PENDIDIKAN ISLAM KLASIK DALAM MEMPERKUAT KUALITAS PENDIDIKAN ISLAM INDONESIA DI ERA KONTEMPORER - Sari, Nia Yunia (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
In this modern era, education is a very important thing to be mastered by every individual. Communities are vying to include their children to qualified schools to get a decent education. Talking about contemporary or modern education can not be separated from the history of Islamic education portrait that brought it into modern education as it is today. The formulation of Islamic education has been established at the time of the Prophet as the forerunner of the birth of education and continues to evolve to the present day. And it should be noted that in its development there is a development of institutions that accompany it as a support activity in learning.